Canine Soft Tissue Sarcoma Managed in First Opinion Practice: Outcome in 350 Cases. Issue 7 (12th April 2014) - Bray, Jonathan P.; Polton, Gerry A.; McSporran, Keith D.; Bridges, Janis; Whitbread, Trevor M.
<x xml:space="preserve">Abstract</x> Objective To determine outcome of dogs with a diagnosis of soft tissue sarcoma managed in first opinion practice. Study Design Retrospective, case‐controlled study Animals Dogs (n = 350) with primary occurrence of a soft tissue sarcoma. Methods A previously validated questionnaire was sent to all veterinarians requesting clinical information and ultimate outcome for all dogs. Histologic sections were reviewed by a single pathologist. Results Most surgeries were unplanned, with only 15 (4%) dogs having a histologic and 59 (16.8%) dogs having a cytologic diagnosis before surgery. Median survival time for all dogs was not reached with 70% proportional survival at 5 years. Local recurrence developed in 73 (20.8%) cases. The extent of resection performed was not associated with improved survival (P = .2) or tumor recurrence (P = .8). Age <8 years (χ2 = 6.1; P = .01), tumors <5 cm in size (χ2 = 9.6; P = .002) and discrete tumors (χ2 = 16.6; P < .001) had improved survival outcomes. On multivariate analysis, a high tumor grade was significant for recurrence (HR 5.8; P < .001; 95% CI: 2.2–14.8). Evidence of a selection bias towards less aggressive tumors being managed in first opinion practice was confirmed. Conclusions Wide resection margins are not the primary determinant of outcome for all soft tissue sarcoma. Veterinarians need to better understand the biologic behavior of a suspected soft tissue sarcoma before treatment to allow surgical margins to be adjusted accordingly.